Faktor â Faktor yang Mempengaruhi Kepuasan Kerja (Studi pada Karyawan Sekolah Tinggi Ilmu FarmasiâYAYASAN PHARMASIâ Semarang) - Melani, Titis; ., Suhaji (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The purpose of this study was to determine the influence of financialfactors, physical factors, social factors and psychological factors on employeesatisfaction of Pharmacy school "pharmaceutical FOUNDATION" Semarang. Thepopulation in this study was employees including lecturers and staff at the School ofPharmacy "pharmaceutical FOUNDATION" Semarang which was also the sample as 94people. The analytical tool used was multiple linear regression. The results showed thatthere was a significant influence either partially or simultaneously of financial factors,physical factors, social factors and psychological factors on employee satisfaction ofschool Pharmacy "pharmaceutical FOUNDATION" Semarang. The coefficient ofdetermination of the four independent variables 45.2% means that the variation of thefour independent variables in explaining job satisfaction was 45.2%, while the rest(100% - 45.2%) = 54.8% was explained by other variables not mentioned in this study.Keywords: Job Satisfaction, Financial, Physical, Social , Psychological.